Exploring Complex Concepts Through Storytelling: A Synchronous Online Health Policy Course Case Study and Recommendations for Implementing Across Disciplines - Corrie Whitmore; Kathryn Schild (Open Praxis, 2022)
Educational experts advocate for storytelling’s community building aspects; it is also a valuable tool for deepening students’ cognitive engagement. Indigenous pedagogy has long emphasized the centrality of storytelling to knowledge production and transmission (Neeganagwedgin, 2020). This article offers a case study analyzing an upper-division undergraduate health policy course transformation to foreground storytelling in a synchronous online format. Consistent with the “watch one, do one, teach one” model, students heard narrative descriptions of guest storytellers’ policy experiences, constructed narrative stories describing a population health problem in written assignments, and shared a policy proposal story about why policy matters and how it can be changed to improve population health. This approach improved student engagement, fostered knowledge creation, and – despite the distance inherent in online education – improved students’ sense of self-efficacy and membership in a professional community. The article concludes with recommendations for integrating storytelling into other disciplines and modalities.